Estimation of Release of Nickel and Chromium by Indian Made Orthodontic Appliance in Saliva - Parashar, Sandeep (J Clin Diagn Res, 2015)
INTRODUCTION: With increasing use of Indian made orthodontic materials, need was felt to know nickel and chromium release from these material. MATERIALS AND METHODS: This study was conducted on simulated appliances consisting of brackets (022″Roth, Modern orthodontics, Ludhiana, India), from second premolar to central incisor, buccal tube and 0.019×0.025- inch SS arch wires secured with SS ligatures. Immersion was done in artificial saliva. Samples were analysed to using Atomic Absorption Photospectrometer (GVC ScientificEquipment Pvt. Ltd Australia) at AES Laboratories (P) Ltd., Noida India on 1(st), 7(th), 14(th) and 28(th) day. RESULTS: SPSS (ver 17, Inc., Chicago, Illinois, USA) was used toperform the statistical analysis. Descriptive statistics i.e. median and 25 and75 percentiles were used. Peak nickel release was on 7(th) day and subsequently declined over 14(th) and 28(th) day. The peak level of chromium concentration was on 14(th) day, which declined thereafter. CONCLUSION: Average daily release of nickel and chromium over a period of one month was 97.368 μg/day and 47.664 μg/day respectively. The estimated release rates were approximately 32% and 16% of the reported average daily dietary.